The application of pseudotypes to influenza pandemic preparedness. (June 2015) - Ferrara, Francesca; Molesti, Eleonora; Temperton, Nigel
ABSTRACT : Human and animal populations are constantly exposed to multiple influenza strains due to zoonotic spillover and rapid viral evolution driven by intrinsic error-prone replication and immunological pressure. In this context, antibody responses directed against the hemagglutinin protein on the surface of the virus are of importance since they have been shown to correlate with protective immunity. Serological techniques, detecting these responses, play a critical role in influenza pandemic preparedness in particular with regard to the measurement of vaccine immunogenicity. As the recent human pandemics (H1N1) and avian influenza outbreaks (H5 and H7) have demonstrated, there is an urgent need to be better prepared to assess the contribution of the antibody response to protection against newly emerged viruses and to evaluate the extent of pre-existing heterosubtypic immunity in populations. This review compares pseudotype-based assays with wild-type and virus-like particle virus assays and discusses their place in the pandemic preparedness against the influenza virus. It additionally addresses the state-of-the-art developments of pseudotype-based assays (chimeric hemagglutinins, multiplex and post-attachment) including the development and future deployment of assay kits and approaches toward standardization to both preclinical and clinical endpoints. Progress toward the development of an influenza pseudotype library for the purposes of pandemic preparedness is also outlined and discussed.